2012
DOI: 10.1007/s00253-012-4490-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of two distinct mycelial populations in liquid-grown Streptomyces cultures using a flow cytometry-based proteomics approach

Abstract: Streptomycetes are proficient producers of enzymes and antibiotics. When grown in bioreactors, these filamentous microorganisms form mycelial pellets that consist of interconnected hyphae. We here employed a flow cytometry approach designed for large particles (COPAS) and demonstrate that liquid-grown Streptomyces cultures consist of two distinct populations of pellets. One population consists of mycelia with a constant mean diameter of approximately 260 μm, whereas the other population contains larger mycelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 51 publications
(59 reference statements)
1
37
0
Order By: Relevance
“…CslA belongs to the glycosyltransferase family 2, which includes cellulose and chitin synthases, among others (32). Deletion of cslA abolishes pellet formation in liquid-grown cultures and also blocks the formation of reproductive aerial hyphae on solid medium (28,29). GlxA is a newly characterized member of the AA5 family of mono-copper oxidase possessing a Tyr-Cys cross-linked redox cofactor (30).…”
mentioning
confidence: 99%
“…CslA belongs to the glycosyltransferase family 2, which includes cellulose and chitin synthases, among others (32). Deletion of cslA abolishes pellet formation in liquid-grown cultures and also blocks the formation of reproductive aerial hyphae on solid medium (28,29). GlxA is a newly characterized member of the AA5 family of mono-copper oxidase possessing a Tyr-Cys cross-linked redox cofactor (30).…”
mentioning
confidence: 99%
“…These include the DosS-like (SCO0203), DosR-like (SCO0204), and DosT-like (SCO0211) genes which represent orthologs of M. tuberculosis, where DosS and DosT act as sensors of redox stress (induced by respiration-impairing gases such as NO) and hypoxia for the DosR transcriptional factor (37). Interestingly, proteome comparisons in S. coelicolor populations of small and large pellets revealed that proteins encoded by genes flanking the dosR-like gene (SCO0204) were overrepresented in large pellets, where a higher level of oxygen stress is assumed to occur (38). In Mycobacterium spp., DosR controls the expression of genes necessary for dormancy survival (32,37).…”
Section: Discussionmentioning
confidence: 99%
“…Actinobacteria, especially streptomycetes, form mycelial pellets or clumps when grown in shaken liquid medium; these clumps consist of interconnected hyphae of different sizes in streptomycetes (van Veluw et al, 2012). Clumps of mycobacteria are formed by aggregates of individual cells (Scherr & Nguyen, 2009).…”
Section: Discussionmentioning
confidence: 99%